PENGARUH PRIOR OPINION, COMPANY GROWTH, DAN MEKANISME CORPORATE GOVERNANCE TERHADAP PEMBERIAN OPINI AUDIT GOING CONCERN - Aulia Choirun Nisa; Rudy Rudy (LPPM Universitas Bina Bangsa, 2023)
This study aims to obtain empirical evidence regarding the influence of Prior Opinion, Company Growth, and Corporate Governance Mechanisms on the provision of Going Concern Audit Opinions. This study uses manufacturing companies listed on the Indonesia Stock Exchange (IDX) for 2016-2021, sampling using a purposive sampling method. From a population of 350 companies, there are a sample of 14 companies with a total of 84 observational data. The analysis technique used is descriptive statistical techniques and panel data regression with the help of Eviews version 12. The results of this study indicate that simultaneously Prior Opinion, Company Growth, and Corporate Governance Mechanisms have an effect on giving Going Concern Audit Opinions and partially Prior Opinions have an effect on giving Going Concern Audit Opinion. Meanwhile, Company Growth and Corporate Governance Mechanisms have no effect on giving a Going Concern Audit Opinion